Sunitinib Inhibits Cell Proliferation and Alters Steroidogenesis by Down-Regulation of HSD3B2 in Adrenocortical Carcinoma Cells - Kroiss, Matthias; Reuss, Miriam; Kühner, Dorothee; Johanssen, Sarah; Beyer, Melanie; Zink, Martina; Hartmann, Michaela; Dhir, Vivek; Wudy, Stefan A.; Arlt, Wiebke; Sbiera, Silviu; Allolio, Bruno; et al. (Frontiers in Endocrinology, 2011)
The multi-tyrosine kinase inhibitor sunitinib is used in the treatment of several solid tumors. Animal experiments pointed to an adrenotoxic effect of sunitinib. Therefore, we evaluated the expression of key targets of sunitinib in human adrenocortical carcinoma (ACC) tumor samples and investigated its in vitro effects in ACC cell lines. We carried out immunohistochemistry for vascular endothelial growth factor (VEGF) and its receptor (VEGF-R2) in 157 ACC samples and 9 normal adrenal glands. VEGF and VEGF-R2 protein were expressed in 72 and 99% of ACC samples, respectively. Using NCI-H295 and SW13 ACC cell lines, we investigated the effects of sunitinib on cell proliferation. Sunitinib reduced dose-dependently cell viability of both NCI-H295 and SW13 cells (SW13: 0.1 µM 96±7%, 1µM 90±9%*, 5µM 62±6%*, controls 100±9%; *p<0.05). To determine sunitinib effects on steroidogenesis, we measured steroid hormones in cell culture supernatant by gas chromatography mass spectrometry. We observed a pronounced decrease of cortisol secretion (1µM 90.1±1.5%*, 5µM 57.2±0.3%*, controls 100±2.4%) and a concomitant increase in the DHEA/4-androstenedione and 17-hydroxypregnenolone/17-hydroxyprogesterone ratios, indicating specific inhibition of 3-hydroxysteroid dehydrogenase (HSD3B2). In yeast microsomes transformed with HSD3B2, no direct inhibition of HSD3B2 by sunitinib was detected. Sunitinib induced down regulation of HSD3B2 mRNA and protein in ACC cell lines (mRNA: 1µM 44±16%*; 5µM 22±2%*; 10µM 19±4%*; protein: 1µM 82±8%; 5µM 63±8%*; 10µM 55±9%*). CYP11B1 was down-regulated at mRNA but not at protein level and CYP11A1 remained unchanged. In conclusion, target molecules of sunitinib are expressed in the vast majority of ACC samples. Sunitinib exhibits anti-proliferative effects in vitro, and appears to specifically block adrenal steroidogenesis by down-regulation of HSD3B2, rendering it a promising option for treatment of ACC.